1987
DOI: 10.1017/s0022112087002222
|View full text |Cite
|
Sign up to set email alerts
|

Bénard-von Kármán instability: transient and forced regimes

Abstract: The wake of a circular cylinder is investigated near the oscillation threshold by means of a laser probe. Above the threshold the transient regime is studied and described by a Stuart-Landau law (already found to be relevant in explaining free-oscillating regimes). Below the critical point, impulse and resonant regimes are examined, so the coefficients of the Stuart-Landau equation are determined.Moreover, in the supercritical regime, the behaviour of the (externally forced) oscillating system is described, va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

30
319
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 501 publications
(350 citation statements)
references
References 24 publications
30
319
1
Order By: Relevance
“…One could imagine to estimate all 15 coefficients using transient dynamics computed by DNS. However, such a procedure, although it has been used successfully for codimension one bifurcations (Provansal et al 1987), is a formidable task no one has ever attempted for multiple codimension problems. In the present study, we carry out a thoroughly analytical asymptotic expansion of the flow field based on the global modes destabilizing the axisymmetric wake.…”
Section: Introductionmentioning
confidence: 99%
“…One could imagine to estimate all 15 coefficients using transient dynamics computed by DNS. However, such a procedure, although it has been used successfully for codimension one bifurcations (Provansal et al 1987), is a formidable task no one has ever attempted for multiple codimension problems. In the present study, we carry out a thoroughly analytical asymptotic expansion of the flow field based on the global modes destabilizing the axisymmetric wake.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of a locally absolutely unstable flow region, in contrast, the flow may bifurcate to a global mode. Prominent examples of flows exhibiting global instability triggered by local absolute instability include the cylinder wake, [4][5][6][7] counterflowing shear layers, 8 swirling jets, 9 and jets with counterflow. 10,11 In the hot jet experiments of Monkewitz et al, 1 selfsustained synchronized oscillations were found to set in as the ambient-to-jet temperature ratio S = T ϱ / T c was lowered below a critical value of 0.73.…”
Section: Introductionmentioning
confidence: 99%
“…These results are confirmed by laboratory experiments. [10][11][12] Experimental 13 and numerical studies 14,15 showed that von Karman streets are a manifestation of a self-sustained oscillation ͑i.e., a global mode͒, associated to a local absolute instability region in the base flow. Hence a first step in order to understand the possible change in the nature of large-scale wake instability is to investigate the absolute versus the convective stability of local profiles.…”
Section: Introductionmentioning
confidence: 99%